PENINGKATAN MENGUNGKAPKAN MONOLOG DESKRIPTIF LISAN MENGGUNAKAN SISTEM ICARE PADA SISWA KELAS VII SMPN 1 KARANGPLOSO - Rike Eliyawati (Universitas Islam Balitar, 2017)
This study aims to improve the skills to express simple descriptive monologue in oral English. The study used a class action research design with three cycles. Conducted in SMPN 1 Karangploso, Malang in September to November 2013, this study assigned 32 students of grade VII as the subject. Data were collected using observation, interview and document. The study revealed that (1) the use of the ICARE system improved skills to express simple monologue descriptive in oral English at level of literacy; (2) characteristics of oral English after ICARE was treated showed an increase showing the use of precise pronunciation, appropriate word choice and grammatical sentences, and (3) students were fluent and felt confidence to express orally simple descriptive monologue.